Native arbuscular mycorrhizal fungi and Albizia saponaria for potential revegetation of tropical asphalt and nickel post-mining areas - Tuheteru, Faisal Danu; Husna, Husna; Nurdin, Wiwin Rahmawati; Wibowo, Surya Edy; Tuheteru, Edy Jamal; Albasri, Albasri; Arif, Asrianti (Brawijaya University, 2026)
Native arbuscular mycorrhizal fungi (AMF) have been shown to effectively enhance the growth and nutrient uptake of Vitex cofassus grown on post-asphalt mining soils. However, their potential needs to be further evaluated across various mining substrates and different tree species. This study aimed to assess the effects of native AMF inoculation on the early growth performance of Albizia saponaria seedlings cultivated on post-asphalt and post-nickel mining soils under greenhouse conditions. A completely randomized design was employed with seven treatments: uninoculated control, Racocetra crispi, Glomus intraradices, Glomus sp., Glomus sp.-LW10, Glomus sp.-SW10, and Mycofer IPB/AMF mixture. Parameters observed after three months of growth included plant height, AMF root colonization percentage, total dry weight, mycorrhizal inoculation effect (MIE), and the uptake of phosphorus (P), nitrogen (N), calcium (Ca), and nickel (Ni). The results indicated that native AMF inoculation significantly improved early growth and total dry weight of A. saponaria seedlings. The highest MIE values were observed in the G. intraradices treatment, reaching 92.73% and 82,9%. Native AMF inoculation also enhanced the uptake of P, N, Ca, and Ni in plant tissues. These findings suggest that local AMF isolates can be effectively utilized to improve seedling quality and accelerate the success of revegetation programs on degraded post-mining lands in Indonesia.